Preaching in pictures : using images for sermons that connect - Jonker, Peter (Peter M.) (Nashville, TN : Abingdon Press, 2015)
"The preacher's words are meant to connect, to resonate with and influence hearers. Too often, sermons fall short. Preaching in Pictures : Using Images for Sermons that Connect shows how to choose, use, and illustrate a controlling image in every sermon. Readers learn how one effective image can cause the proclaimed word to sink in and transform the listener. Peter Jonker helps readers build skills and confidence with practical instruction, examples, and straighforward teaching." --From Publisher's description.
The controlling image -- Controlling images: a field study -- What preachers can learn from poets -- Learning from marketers and visual artists -- How to find a controlling image -- Sermons and image on screens.
Includes bibliographical references.
Keywords: Preaching; Image (Theology); Homiletical illustrations